2021
DOI: 10.1200/po.20.00151
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Epigenetic Landscape of Lung Adenocarcinoma Links HOXB9 DNA Methylation to Intrinsic EGFR-TKI Resistance and Heterogeneous Responses

Abstract: PURPOSE Epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) show efficacy in treating patients with lung adenocarcinoma with EGFR-activating mutations. However, a significant subset of targeted patients fail to respond. Unlike acquired resistance (AR), intrinsic resistance (IR) remains poorly understood. We investigated whether epigenomic factors contribute to patient-to-patient heterogeneity in the EGFR-TKI response and aimed to characterize the IR subpopulation that obtains no benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The hyper-methylation status at transcriptional regulatory regions of those genes indicated their expression was suppressed in cases with EGFR dependent resistance mutations. Our finding was consistent with a recent study by Shu et al 48 showing that increased methylation of HOXB9 correlated with higher rate of resistance to EGFR-TKI. Thus, such consistent findings indicated that the hyper-methylation status of HOX genes could be exploited to predict and treat EGFR amplification mediated resistance.…”
Section: Discussionsupporting
confidence: 93%
“…The hyper-methylation status at transcriptional regulatory regions of those genes indicated their expression was suppressed in cases with EGFR dependent resistance mutations. Our finding was consistent with a recent study by Shu et al 48 showing that increased methylation of HOXB9 correlated with higher rate of resistance to EGFR-TKI. Thus, such consistent findings indicated that the hyper-methylation status of HOX genes could be exploited to predict and treat EGFR amplification mediated resistance.…”
Section: Discussionsupporting
confidence: 93%
“…EGFR mutation promotes the expression of EGR1, 76,77 and high early growth response 1 (EGR1) expression correlates with resistance to anti‐EGFR treatment 78 . A higher level of DNA methylation of HOXB9 was found to be correlated with intrinsic EGFR‐TKI resistance and poor TKI response 79 . Expression of mutant EGFR (EGFRvIII) resulted in upregulation of a small group of genes, including FOSL1, 80 and EGFR‐PKM2 signalling induced the expression of FOSL1 to promote nasopharyngeal carcinoma cell invasion and metastasis 81 .…”
Section: Resultsmentioning
confidence: 97%
“…78 A higher level of DNA methylation of HOXB9 was found to be correlated with intrinsic EGFR-TKI resistance and poor TKI response. 79 Expression of mutant EGFR (EGFRvIII) resulted in upregulation of a small group of genes, including FOSL1, 80 and EGFR-PKM2 signalling induced the expression of FOSL1 to promote nasopharyngeal carcinoma cell invasion and metastasis. 81 Our results will help to improve the response to EGFR-TKI treatment.…”
Section: Status Of Pdl1-or Egfr-modified Gene Signatures Of Epithelia...mentioning
confidence: 99%
“…A less common methylation-associated mechanism was found to be involved in the generation of T790M mutation that was induced by the activity of cytidine deaminase (AICDA) expression [ 65 ]. Very recently, a genome-wide DNA methylation analysis revealed that HOXB9 DNA methylation was linked to intrinsic EGFR-TKI resistance and complementary to mutation profiling could discern whether lung adenocarcinoma patients would benefit from EGFR-TKI treatment [ 66 ]. However, all these studies were performed in lung cancer cell lines or primary tissues and have not thus compared DNA methylation status before and after treatment.…”
Section: Discussionmentioning
confidence: 99%